The Comparison of Regional RNFL and Fundus Vasculature by OCTA in Chinese Myopia Population - Yuanjun Li; Hamza Miara; Pingbo Ouyang; Bing Jiang (Journal of Ophthalmology)
Purpose. To determine the correlations between peripapillary vessel density, retinal nerve fibre layer (RNFL) thickness, and myopic indices at retina quadrants with optical coherence tomography angiography (OCTA) in Chinese. Methods. Fifty-six subjects with a mean spherical equivalent (MSE) of −3.63 ± 0.29 D were included. Peripapillary RNFL thickness and retinal vessel density in four sectors (superior, nasal, inferior, and temporal quadrants) were determined by OCTA, and correlations of the main outcomes were analyzed. Results. Negative correlations were found between the peripapillary RNFL thickness and axial length (AL) at superior (r=−0.335, P=0.001) and inferior (r=−0.551, P<0.001) quadrants. There was a significant positive correlation with spherical equivalent (SE) at the corresponding quadrants as well as at the nasal quadrant (r=0.339, P=0.001; r=0.379, P<0.001; and r=0.209, P=0.039, resp.). Peripapillary retinal vessel density was also negatively correlated with AL at the nasal quadrant (r=−0.392, P<0.001), and only at the nasal quadrant, there was a positive correlation between the peripapillary vessel density and SE (r=0.319, P=0.001). Conclusions. The degree of myopia and elongation of AL were negatively correlated with peripapillary RNFL thickness at superior and inferior quadrants and with peripapillary retinal vessel density at the nasal quadrant.